Physicochemical Profile of Canastra Cheese Inoculated with Starter Cultures of Kluyveromyces lactis and Torulaspora delbrueckii - Adriele do Amor Divino Silva; Dérica Gonçalves Tavares; Rafaela Pereira Andrade; Tamara Leite dos Santos; Whasley Ferreira Duarte (Foods)
Canastra cheese, an artisanal cheese produced in Serra da Canastra—Brazil, has great cultural importance. Furthermore, this cheese has nutritional and sensory attributes that make it of great economic importance. Its microbiota is composed of different bacteria and yeasts. Some yeasts already isolated by our research group have been characterized as potential probiotics. Probiotic microorganisms have garnered scientific interest, as improvements in the physical, chemical and sensory characteristics of food products have been reported when these microorganisms are used. In this context, the objective of this work was to evaluate Kluyveromyces lactis and Torulaspora delbrueckii, which were previously isolated from Canastra cheese, as autochthonous starter cultures. Canastra cheese was produced under three different conditions: (1) cheese with “Pingo” (natural starter), (2) cheese with “Pingo” + yeast mixed culture, and (3) cheese with only mixed yeast culture. The results showed that the mixed yeast inoculum significantly influenced the lactic acid bacteria population. Yeast populations remained at around 106 CFU/g after 45 days of maturation. Furthermore, cheeses containing the yeast mixed with inoculum had an initial lactose content reduced by 92.80% compared to cheese produced with “Pingo” (87.70%). The antioxidant activity, evaluated using the ABTS method, showed that cheeses containing the mixed yeast culture had higher percentages of antioxidant activity at 45 days of maturation. The texture profile of the cheeses changed over time. In general, the cheese containing the yeast mixed culture and “Pingo” and the cheese containing “Pingo” had the lowest hardness at 30 days of maturation (5245 and 5404 N, respectively). Among the volatile compounds, 3-methylbutyl octanoate, phenethyl butyrate, phenethyl propionate, isobutyl butanoate and pentyl propionate were found only in cheeses produced with yeast mixed culture. The obtained results demonstrated that the use of autochthones probiotic cultures could improve the cheese characteristics without negatively impacting the traditional physicochemical attributes of Canasta cheese.